2020
DOI: 10.3389/fgene.2020.602485
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Critical m6A RNA Methylation Regulators as Malignant Prognosis Factors in Prostate Adenocarcinoma

Abstract: RNA methylation accounts for over 60% of all RNA modifications, and N6-methyladenosine (m6A) is the most common modification on mRNA and lncRNA of human beings. It has been found that m6A modification occurs in microRNA, circRNA, rRNA, and tRNA, etc. The m6A modification plays an important role in regulating gene expression, and the abnormality of its regulatory mechanism refers to many human diseases, including cancers. Pitifully, as it stands there is a serious lack of knowledge of the extent to which the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 78 publications
(94 reference statements)
1
24
0
Order By: Relevance
“…In addition, the results found that YTHDF1, YTHDF2, and YTHDC2 exhibited a positive correlation, but METTL14, FTO, and ALKBH5 were negatively correlated to Gleason grades (Wu et al, 2021). Some researchers analyzed the important m6A RNA regulators, which act as prognosis factors in prostate cancer, and identified RBMX, NXF1, YTHDF1, HNRNPA2B1, and TRMT112 as critical genes that have great effects on the prognosis of PCa patients (Xu et al, 2020). Many studies have also explored expression patterns and clinical prognostic values of m6A regulators in PCa, which plays a great function in the treatment of PCa (Ou- Yang et al, 2020;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results found that YTHDF1, YTHDF2, and YTHDC2 exhibited a positive correlation, but METTL14, FTO, and ALKBH5 were negatively correlated to Gleason grades (Wu et al, 2021). Some researchers analyzed the important m6A RNA regulators, which act as prognosis factors in prostate cancer, and identified RBMX, NXF1, YTHDF1, HNRNPA2B1, and TRMT112 as critical genes that have great effects on the prognosis of PCa patients (Xu et al, 2020). Many studies have also explored expression patterns and clinical prognostic values of m6A regulators in PCa, which plays a great function in the treatment of PCa (Ou- Yang et al, 2020;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five m6A RNA methylation were collected from the m6A2target database 3 ( Deng et al, 2021 ) and literatures ( Tu et al, 2020 ; Xu et al, 2020 ). The expression matrixes of these 25 m6A genes were retrieved from the TCGA, including the expression regulatory factors of writers (METTL3, METTL14, METTL16, CBLL1, ZCCHC4, WTAP, VIRMA, ZC3H13, RBM15, and RBM15B), readers (YTHDC1, YTHDC2, YTHDF1, YTHDF2, YTHDF3, HNRNPC, FMR1, RBMX, HNRNPA2B1, LRRPRC, IGF2BP1, IGF2BP2, and IGF2BP3), and erasers (FTO and ALKBH5).…”
Section: Methodsmentioning
confidence: 99%
“…Both m6A enzymes and lncRNAs are ideal diagnostic and prognostic markers. Accumulating evidence shows that m6Arelated mRNAs and lncRNAs can serve as novel potential targets to predict the prognosis for multiple cancers (Barros-Silva et al, 2020;Li et al, 2020;Meng et al, 2020;Xu et al, 2020Xu et al, , 2021Jin et al, 2021). For instance, METTL14 is a prognosis-associated regulator of m6A RNA methylation in hepatocellular carcinoma (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%